2000
DOI: 10.1007/s004210000302
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency oscillations of the heart rate during ramp load reflect the human anaerobic threshold

Abstract: The aim of this study was to analyze the dynamic behavior of the high-frequency component (HF > 0.15 Hz) of heart rate variability (HRV) and the respiratory frequency in relation to the anaerobic threshold (AT). Twenty-two healthy subjects [mean (SD) age: 24 (6) years, height: 175 (10) cm, body mass: 65 (11) kg] completed a ramp load, with increments of 20 W x min(-1), on a cycle ergometer. The AT was determined by the V-slope-method. Respiratory movements of the thorax, and the electrocardiogram were monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 23 publications
6
56
1
4
Order By: Relevance
“…This procedure is necessary since RRseries are irregularly sampled, due to the physiological variability of the heart activity, and an evenly-distributed sampled series is a mandatory condition in several analyses. Then, since the RR interval sampling frequency is usually chosen among 2, 4, 6, 8 and 10 Hz [107], we decided to obtain a sampling frequency equal to 10 Hz as performed in [108,109]. In fact, according to [107], it is important to highlight that the bandwidth within which the autonomic nervous system has a significant response is 0-1 Hz.…”
Section: Heart Rate Variability Estimationmentioning
confidence: 99%
“…This procedure is necessary since RRseries are irregularly sampled, due to the physiological variability of the heart activity, and an evenly-distributed sampled series is a mandatory condition in several analyses. Then, since the RR interval sampling frequency is usually chosen among 2, 4, 6, 8 and 10 Hz [107], we decided to obtain a sampling frequency equal to 10 Hz as performed in [108,109]. In fact, according to [107], it is important to highlight that the bandwidth within which the autonomic nervous system has a significant response is 0-1 Hz.…”
Section: Heart Rate Variability Estimationmentioning
confidence: 99%
“…To determine this, a new non-invasive method has been studied due to evidence of good correlation with both the lactate threshold 13 and with the so-called productmoment with respect to the values of VO 2 in incremental testing 14 . This is the HRVt, which allows the detection of the precise AT occurrence timing (threshold 1) for the development of continuously increasing exercise protocols and to support this new proposal, it has been demonstrated that nonlinear methods aimed at analysis of HRVt in physical exertion can also provide consistent results on the cardiac autonomic modulation 13,15,[21][22][23] . Lima and Kiss 13 reported that during incremental exercise, the progressive decrease of SD1 (standard deviation of O and MO, 14.3 ± 3.1, 7.9 ± 4.3 and 7.5 ± 2.1; with p < 0.05 between NO and MO.…”
Section: O (Meters)mentioning
confidence: 99%
“…Este achado corrobora a relação entre o limiar determinado pela VFC e a resposta metabólica de condição estável da concentração sanguínea de lactato. No entanto, embora outros estudos tenham indicado a possível relação entre a resposta da VFC e o LV 1 (ALONSO et al, 1998;ANOSOV et al, 2000;COTTIN et al, 2006;TULPPO et al, 1996) e o primeiro limiar de lactato (LIMA; KISS, 1999), o presente estudo indica uma possibilidade de proximidade do LVFC, como determinado por Lima e Kiss (1999), com o segundo limiar, uma vez que a carga constante correspondente ao LVFC conduziu a valores de lactato próximos e acima de 4 mmol.l -1 para 50% dos sujeitos, e não próximos a 2 mmol.l -1 , como seria a expectativa para o primeiro limiar (RIBEIRO, 1995). Valores em torno de 4 a 6 mmol.l -1 têm sido observados na carga de máximo estado estável de lactato em exercícios realizados em ciclos ergométricos por sujeitos treinados e que praticam atividade física de maneira recreacional (BENEKE;HUTLER;LEITHAUSER, 2000;BENEKE et al, 2003;FIGUEIRA et al, 2007), reforçando a hipótese de que nossos achados indicam uma possível relação da carga deste limiar da VFC com a maior carga em condição de estabilidade do lactato.…”
Section: Ab -Lvfc Lvfc Ac -Lvfcunclassified
“…Em seguida, outros estudos verificaram a relação entre limiares da VFC determinados por diferentes métodos e o LV 1 , identificando similaridades entre os valores e/ou correlação significativa entre estas variáveis (ANOSOV et al, 2000;COTTIN et al, 2006). Cottin et al (2006) demonstraram que também o segundo limiar ventilatório (LV 2 ) poderia ser determinado a partir da análise da VFC no domínio da freqüência.…”
Section: Introductionunclassified